3 - The State and Labour Control in Malawi: Continuities and Discontinuities Between One-party and Multiparty Systems: DOI: 10.4314/ad.v30i4.22240 - Dzimbiri, Lewis B. (Africa Development, 2005)
An analysis of state-labour relations in Malawi over a period of four decades reveals, like in other countries in Southern Africa, tendencies towards continui ties and discontinuities in labour controls. While Malawi's political system has undergone a major transformation to democracy in the 1990s after three dec ades of dictatorship which was hostile to trade unions through administrative, political and legal apparatuses, the democratic state has been marked by 'diplo matic' hostility through divide-and-rule and hide-and-seek tactics. Using differ ent means the state has succeeded in curtailing freedom of association in varying degrees during the one-party and multiparty periods. Thus, while labour control as an objective of the state has not changed, the means have changed dramatically. The desire to achieve political stability and economic develop ment, against a changed international political order demanding human rights and good governance in the 1990s, explains the current 'diplomatic' hostility in Malawi's industrial relations. The role of the international donor community in exporting democratic structures and values to societies that do not have an in built culture of democracy similar to western societies is viewed as a further explanation for the creation of significant degrees of discrepancies between la bour policy and practice in Malawi.